TSUNAMIGENIC SOURCES IN THE BAY OF PLENTY, NEW ZEALAND - Roy A. Walters (Science of Tsunami Hazards, 2006)
New Zealand sits in a precarious position astride the boundary between the Pacific and Australian Plates. There is a wide range of potential tsunamigenic sources in this area including fault movements, submarine landslides, volcanic activity, and other mechanisms. In addition, considerable prehistoric information indicates that large tsunamis have inundated the coastline several times in the past. A part of our work has been directed toward using historic and prehistoric tsunami data to evaluate possible sources. Several types of dislocation models and submarine landslide models are used to simulate the displacement of the sources. A finite element numerical model is used to simulate generation, propagation and runup of the resultant tsunami. As an example, we present results for the Bay of Plenty, northeast coast of the North Island, New Zealand. The range of source types includes local faults, subduction zone rupture, volcanic eruptions, sector collapse of seamounts, and submarine landslides. A likely major source is a subduction zone event along the Tonga-Kermadec Trench. Data from paleotsunami deposits have guided the model in determining appropriate source characteristics and establishing the most significant event for this region.